Implementation of Role Playing Method to Include Honesty Values in Early Childhood at RA Darurrasyid Pameungpeuk - Yuliantini; Yusriah; Rohmat, Yusuf; Sari, Yuni Nur Indah (Jurnal Cendekia Islam Indonesia, 2025)
Early childhood character education is very important in shaping children's morals and personalities. One of the character values ​​that need to be instilled is honesty, which is the basis for building a positive attitude and integrity. This study aims to analyze the application of the Role Playing method in instilling the value of honesty in early childhood at RA Darurrasyid Pameungpeuk. The Role Playing method was chosen because it allows children to learn through direct experience, so that they can understand the meaning of honesty better. This study uses a qualitative approach with observation, interview, and documentation techniques to collect data from teachers and students. The results of the study showed that the Role Playing method was effective in improving children's understanding of the value of honesty. Children become more aware of the importance of being honest in everyday life, both at school and at home. In addition, this method also helps improve children's social interaction, self-confidence, and communication skills in expressing their feelings and opinions openly. Thus, the application of the Role Playing method can be an effective strategy in character education in early childhood education institutions. This study is expected to contribute to educators in developing interactive learning that is fun and meaningful for early childhood.